PREOPERATIVE AND POSTOPERATIVE ANTIBIOTIC PROPHYLAXIS IN GYNECOLOGICAL PATIENTS DEPENDING ON INDIVIDUAL RISK FACTORS - A. G. Kedrova; S. A. Levakov; N. S. Vanke (Опухоли женской репродуктивной системы, 2018)
Pelvic inflammatory diseases as complications of invasive diagnostics and surgical treatment occur often enough in patients with gynecological disorders. The risk of infectious complications is always individual and depends on many factors. The implementation of a personified approach and optimization of antibacterial prophylaxis can decrease the incidence of inflammatory reactions and reduce the risk of infectious complications. Objective: to estimate the efficacy and tolerability of combiflox (ornidazole 500 mg + ofloxacin 200 mg) in long-term antibiotic prophylaxis after gynecological and oncological surgeries. Materials and methods. We assessed the results of a 7-day oral course of combiflox after intravenous intraoperative antibiotic prophylaxis (ciprofloxacin 500 mg + metronidazole 500 mg) in 73 women that underwent gynecological or oncological surgeries. All patients were monitored for postoperative complications, including any wound inflammation, low-grade hyperthermia, symptoms of postoperative vaginitis, endometritis, limited peritonitis, adnexitis. Results. We found that 43.8 % of patients were at high risk of developing postoperative inflammatory complications; in most of the cases, it was associated with obesity (body mass index >30 kg/m2). Three out of 32 overweight patients (9.3 %) developed postoperative complications, whereas none of the 41 patients with minimal risk factors had such events. No combiflox-related adverse effects were observed during the study. All patients reported good tolerability and high convenience of the drug. Conclusion. The need for long-term antibiotic prophylaxis depends on the type of surgery and individual risks for infectious complications. Low-cost oral therapy with combiflox (ornidazole + ofloxacin) during the postoperative period reduces the risk of infectious complications, especially among patients with a body mass index >30 kg/m2, since they are particularly prone to wound complications.